(untitled) (Journal of Informatics Education and Research, 2024)
Human race has an inborn tendency to cooperate, compete and conflict, which form very essence of sports. Sports teach a human to work together and coordinate with others to achieve the desired goals. But the most important element of sports is competition. The degree of competition has grown exponentially with the advent of commercialization of sports and aligned activities and hence the increase in disputes. Considering that the sportsperson’s career is of very short span, and the opportunity to represent the country at big events comes to many once in a lifetime, a faster and effective dispersal of the cases will not only save the sportsperson’s career but also may result into more glory in global events. The research discusses the possibilities and the outcomes of setting up of Sports Tribunal in India for effective settlement of disputes in sports.